Determinantes sociais, econômicos e consumo de açúcares: Perspectiva sindêmica para cárie, doença periodontal e outras doenças não transmissíveis em adolescentes - LADEIRA, Lorena Lúcia Costa (2022)
Caries and periodontal disease are the most prevalent noncommunicable diseases (NCDs) worldwide. Despite advances in knowledge on the etiopathogenesis of these oral diseases, accompanied by the evolution of high-tech dental treatments; paradoxically, there was a timid reduction in the prevalence of untreated carious lesions, of only 2,6% in the last three decades. For periodontal disease, there was even an increase in prevalence in this same period. Caries and periodontal disease have different pathophysiology and affect different dental tissues, but these diseases share common factors, such as social vulnerability and behavioral risk factors, such as sugar consumption. These social and behavioral risk factors are also common to systemic NCDs. Although oral NCDs are not directly implicated in increased cases of mortality, they are capable of predicting diabetes decades earlier. In the individual's life cycle, the diagnosis of caries can already be made in early childhood, preceding the diagnosis of periodontitis by at least one or two decades. In temporal sequence, the two oral diseases and their major problem, tooth loss, are able to predict diabetes decades earlier. Periodontitis and diabetes are chronic diseases that evolve in the form of a continuum, a cascade of progressive events between its first signs, the diagnosis, and the collapse of the target organ. Thus, we hypothesize that earlier events of insulin resistance, which are precursors of diabetes, would already be associated with the onset of periodontal disease in adolescents. CHAPTER I of this thesis was the original article “Precursors of insulin resistance underlying periodontitis in adolescents aged 17 to 18 years”, which aimed to analyze the associations between markers of insulin resistance and periodontitis in adolescents, exploring a complex model, adjusted for sex, social determinants, alcohol consumption, smoking, plaque index, and adiposity. This was a representative population based study of adolescents aged 17-18 years from public schools in São Luís, Brazil (n = 405). Insulin resistance was assessed using the Insulin Resistance Index Homeostasis Assessment Model (HOMA-IR) and the triglycerides/HDL-cholesterol ratio (TG/HDL-c). The outcome was Early Periodontitis, a latent variable estimated by the shared variance between bleeding on probing (BoP), probing depth (PD) ≥ 4 mm, and clinical attachment level (CAL) ≥ 4 mm. The association between insulin resistance and periodontitis was modeled through pathways triggered by Socioeconomic Status, Smoking, Alcohol, and Adiposity, using Structural Equation Modeling (SEM). As a result, markers of insulin resistance were associated with early signs of periodontal degradation among adolescents, suggesting that the relationship between diabetes and periodontitis may begin much earlier than has been studied in adult life. The original article “Precursors of insulin resistance underlying periodontitis in adolescents aged 17-18 years” was published in the journal Oral Diseases, Factor de Impacto 4.068, doi: 10.1111/odi.14283, 2022, which had the partnership of three researchers abroad (Aarhus University- Denmark and University British of Columbia- Canada). Our research group has consistently shown that caries and periodontal disease indicators are correlated with each other, forming the phenomenon Chronic Oral Disease Burden in children and adolescents. It should be noted that the Chronic Oral Disease Burden is not a diagnostic measure, but an opportunity to understand caries and periodontal disease in a more integrated way, with a transdisciplinary vision for oral health. Important international organizations have established limits of the daily consumption of sugars for the prevention of NCDs, but these have not yet been tested in association with the Chronic Oral Disease Burden. Our second hypothesis in the thesis was that the limits of sugar intake indicated by international institutions as a risk for NCDs would increase the Chronic Oral Disease Burden in young people. CHAPTER II of this thesis was the original article “Sugar consumption above international recommendations and the burden of oral diseases: a population based study”, which aimed to evaluate the association between the consumption of added sugars above the daily limit of Risk for NCDs and the Chronic Burden of Oral Diseases in Adolescents. This was a population-based cross-sectional study, nested within the RPS cohort, São Luís, Brazil. The study used data from the second follow-up of the cohort, with young people aged 18 to 19 years (n = 2,515). High consumption of added sugars was estimated according to the limits of the World Health Organization (WHO) guidelines (≥5% of total energy/day) and the American Heart Association (AHA) (≥25g/day). Chronic Oral Disease Burden was a latent variable (number of decayed teeth, PS ≥4mm, NIC ≥3mm and SS). Models were adjusted for Socioeconomic Status, gender, obesity and plaque index and analyzed by SEM. Sugar intake among young people was well above international risk recommendations for NCDs, and was associated with the Chronic Oral Disease Burden. Doses reduced to half of the guidelines were also associated with some parameters of caries and periodontal disease, making us reflect that there may not be safe exposures for consumption of these sugars. The original article “Sugars intake above international recommendations and oral disease burden: a population-based study” was accepted for publication in the journal Oral Diseases, Factor de Impacto 4068, in November 2022 and had the participation of two researchers from abroad (National Dental Research Institute Singapore). The first two chapters of this thesis led us to understand more about the groupings between oral and systemic NCDs, and the role of social determinants and risk behaviors in this process. Syndemic is the interaction of social and environmental factors resulting in a synergistic burden of excess disease, which has been recommended to address comorbidities, especially among NCDs. A syndemic approach has yet to be explored from an oral health perspective. The third hypothesis raised in the thesis was that socioeconomic determinants interact with risk behaviors, such as greater exposure to added sugars, and result in the syndemic clustering of NCDs, a phenomenon observable in young people. CHAPTER III of this thesis was the original article “Social vulnerability and addictive behaviors: a syndemic model linking obesity, insulin resistance with caries and periodontitis in Brazilian adolescents”, which aimed to analyze obesity, insulin resistance and chronic oral diseases (caries and periodontal disease) from a syndemic perspective, considering pathways triggered by socioeconomic status, high consumption of sugar, smoking and alcohol in adolescents. This was a population-based study that analyzed the 18–19-year follow-up of the RPS Cohort, São Luís, Brazil (n=2,515). We investigated the grouping of obesity, Insulin Resistance Phenotype (latent variable formed by the indicators: TG/HDL-c, TyG and VLDL c) with the Chronic Oral Disease Burden (latent variable formed by the indicators: caries, BoP, PD ≥ 4mm, CAL ≥3mm, and visible plaque index ≥15%). Social vulnerability was the most ancestral variable represented by the Socioeconomic Status variable, influencing all model variables. The exposure of interest was represented by Addictive Behaviors, a latent variable formed by the consumption of added sugar, smoking and alcohol abuse. Data were analyzed by SEM. As a result, we identified a grouping of the Insulin Resistance Phenotype with obesity and with the Chronic Oral Disease Burden at the end of the second decade of life. Our results support a paradigm shift in coping with oral diseases in a more transdisciplinary way, based on a syndemic approach, directing efforts towards socioeconomic determinants and behavioral risk factors common to all NCDs. This original thesis article will be defended and subsequently submitted to the Journal of Dental Research. The results of the science produced by this thesis needed to reach society, and so to give visibility to our research findings and ensure the transfer of knowledge to dental surgeons, we prepared the Instructional Resource in digital format, presented as CHAPTER IV of this thesis, entitled “Preventive approach to the common causes of oral and systemic non communicable chronic diseases: the leading role of the dental surgeon in the family health team”, with the objective of highlighting the role of the dental surgeon in the prevention of NCDs, based on the knowledge of the common risk factors between oral and systemic NCDs. The resource is supplementary material for the e-course “Dental Care for Patients with Chronic Noncommunicable Diseases in Primary Care” offered by UNASUS, in the MOOC (Massive Open Online Course) modality, funded by the Ministry of Health, and which has already trained more than 15 thousand dentists from the SUS network. In the SUS network, the dental surgeon must contribute to the elaboration of public health strategies in primary care for the integrated prevention of oral diseases and other NCDs with higher mortality, with resource savings, improvements in the quality of services and improvement in the quality of life of the population. In this perspective, we prepared a book in digital format, Editora EDUFMA, ISBN: 978-65-5363-070-3, presented as CHAPTER V of this thesis, hosted on the ARES Platform, entitled “Chronic noncommunicable diseases: risk factors and oral health care networks”, which aimed to contribute to the understanding of risk factors for NCDs in the Health Care Network in the Unified Health System (SUS), available free of charge through the link https://ares.unasus.gov.br/acervo/handle/ARES/27070, launched in June 2022, with 266 downloads until November 2022. To contribute to the dissemination of the integrated approach to caries, periodontal disease and other NCDs, a book in digital format was prepared and will be launched in December 2022 by EDUFMA and made available on the ARES Platform, with CHAPTER VI of this thesis, entitled “Caries, periodontitis and other noncommunicable diseases: a transdisciplinary approach for the dental surgeon”. This resource aimed to disseminate the phenomenon Chronic Oral Disease Burden among dentists, from a transdisciplinary view of caries and periodontal disease, discussing the role of social and economic determinants, in addition to common behavioral risk factors for NCDs, with an emphasis on the harmful effects of ultra-processed foods, especially added sugars. In summary, the research results of this thesis showed that oral NCDs, caries and periodontal disease have their indicators grouped in young people forming the Chronic Oral Disease Burden, explained by social determinants and the excessive consumption of added sugars. We also showed that the consumption of added sugars among young people was alarming, far exceeding the limits presented by international organizations, which puts them at future risk of NCDs. In addition, we observed a syndemic picture in young people, with clustering of obesity and early signs of insulin resistance (precursor of diabetes) in association with the Burden of Chronic Oral Diseases, which was explained by social determinants and risk behaviors that were also clustered (smoking, alcohol consumption and sugar consumption). The dental surgeon must have a prominent role in coping with NCDs, since he is a professional in earlier contact with the first signs of these diseases, performing, proposing and supporting more effective interventions and policies in health. To contribute to this professional, we created three instructional resources, to qualify the professional who will be essential in the actions of coping with oral and systemic NCDs in a more integrated way. The SIX CHAPTERS of this thesis are contents aligned with the Strategic Action Plan for Combating Chronic Diseases and Noncommunicable Diseases (2021-2030) of the Ministry of Health and in line with the Sustainable Development Goals (SDGs), and may contribute to a target of reduce, by 2030, premature mortality from NCDs by one third, through prevention and treatment.